Searching for published protocols of randomized controlled trials in primary health care: an empirical systematic approach - Evridiki Papagiannopoulou; Christina Antoniadou; Eleni Ntalaouti; Evangelia Ntzani; Konstantinos Siamopoulos; Athina Tatsioni (James Cook University, 2020)
Introduction: Electronic search filters on family medicine or general practice studies have been developed and validated in previous work. However, there has been no systematic effort to specifically identify and record protocols of randomized controlled trials (RCT) protocols in primary health care (PHC). The aim of the present study was to systematically identify published RCT protocols in PHC and capture information about specific protocol characteristics that may describe this field. Methods: PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Scopus from inception to December 2014 were systematically searched. Protocols of RCTs that were published in English and were relevant to PHC were considered as eligible. Protocols referred either to a mixed population, or to an intervention including a specialized part as well as pilot or feasibility trial protocols, were excluded. Specific protocol characteristics including publication year, country, prospective registration, funding, and publication sources were extracted. Results: The final database included 628 published RCT protocols (median publication year 2011; interquartile range 2009-2013). The majority of protocols were designed in the UK (n=141, 22.5%), the Netherlands (n=105, 16.7%), and USA (n=93, 14.8%). Research was mainly funded by the government (n=408, 65.0%) while 45 protocols (7.2%) included industry as the funding source. Two registries - International Standard Randomised Controlled Trials Number Registry (245 (42.9%)) and ClinicalTrials.gov (209 (36.6%)) - indexed most of the protocols. Journals from several scientific fields published the articles; the field of 'Primary Health Care Medicine, General and Internal' included 69 (11.0%) articles. Conclusion: A compilation of published RCT protocols on PHC was feasible. The majority of protocols on PHC were published over the past 10 years, funded by the government and designed in three main countries.